Pengaruh Pengangguran, Ipm, Dan Bantuan Sosial Terhadap Kemiskinan Di Provinsi Jawa Timur - Lisa Agustin (Fakultas Ekonomi Universitas Kadiri, 2022)
The purpose of this study was to determine the effect of the unemployment rate, human development index, and social assistance on poverty in 38 Regencies/Cities of East Java Province in 2018 to 2020. The data analysis used in this research is panel data. The data time series used are from 2018 to 2020 and the data cross section used are 38 regencies/cities in East Java Province. The model chosen in this study is the Fixed Effect Model (FEM). In this study it was found that unemployment and HDI had an effect on poverty in East Java Province, while social assistance had no effect on poverty in East Java Province.Â Â